Health and well-being in eye care practice: Making the difference in your patient's life. Issue 1 (January 2021) - Retallic, Neil; Shah, Sheena
Abstract : Neil Retallic and Sheena Shah ask the question 'Should we as ECPs be doing more to understand the well-being of our patients?'.